Respuesta :
Point distance formula:
d=√((x_2-x_1)²+(y_2-y_1)²)
Substitute
d=√((3-(-3))²+(2-(-1)²)
Simplify
d=√((6)²+(3)²)
d=√(36+9)
d=√(45)
d=3√(5)
-Hunter
Given :-
- (x 1 , y1) = (-3 , -1)
- (x2 , y2) = (3 , 2)
[tex] \\ \\ [/tex]
To find:
- Distance between two points
We know :-
[tex] \bigstar \boxed{ \rm d = \sqrt{(y_2 - y_1 {)}^{2} + (x_2 - x_1 {)}^{2} } }[/tex]
So:-
[tex] \dashrightarrow \sf d = \sqrt{(y_2 - y_1 {)}^{2} + (x_2 - x_1 {)}^{2} } \\ [/tex]
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf d = \sqrt{(2 - ( - 1) {)}^{2} + (3 - ( - 3) {)}^{2} } \\ [/tex]
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf d = \sqrt{(2 + 1 {)}^{2} + (3 + 3{)}^{2} } \\ [/tex]
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf d = \sqrt{(3 {)}^{2} + (3 + 3{)}^{2} } \\ [/tex]
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf d = \sqrt{(3 {)}^{2} + (6{)}^{2} } \\ [/tex]
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf d = \sqrt{9 + (6{)}^{2} } \\ [/tex]
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf d = \sqrt{9 +36 } \\ [/tex]
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf d = \sqrt{45} \\ [/tex]
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf d = \sqrt{3 \times 3 \times 5} \\ [/tex]
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf d =3 \sqrt{5} [/tex]
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \sf d =3 \times 2.23[/tex]
[tex] \\ \\ [/tex]
[tex] \dashrightarrow \bf d =6.70[/tex]
[tex] \\ \\ [/tex]
[tex] \therefore \underline{ \textsf{ \textbf{distance \: between \: two \: points \: is \: equal \: to \red{6.70 \{approx\}}}}}[/tex]